P283 Hyperpolarised Gas MRI – a pathway to Clinical Diagnostic Imaging. (12th November 2015) - Wild, JM; Collier, G; Marshall, H; Smith, L; Norquay, G; Swift, AJ; Horn, FC; Chan, F; Stewart, NJ; Hutchison, LC; Rao, M; Sabbroe, I; et al.
Abstract : Introduction: Despite the excellent functional sensitivity of hyperpolarised gas MRI to early lung disease, clinical uptake of the technique has to date been hindered by patents, regulatory classification, availability of 3 He and access to polariser technology. However, many of these constraints have been alleviated in recent years, and 129 Xe MRI is now providing high quality lung images at relatively low cost. In January 2015 UK regulatory approval for the manufacture of hyperpolarised gases for routine clinical lung imaging was obtained in Sheffield. Here we present a case series as an overview of the clinical questions that this technology can help resolve in various respiratory indications. Methods: More than 20 patients (aged 13 to 74) have been clinically referred to date with HP gas MRI in Sheffield to date from NHS hospitals across the UK. Clinical histories include non-CF bronchiectasis (scanned before and after a 2 week course of IV antibiotics), COPD for consideration for LVRS/EB valves, complex asthma (scanned before and after bronchodilator inhalation), CF, patients with poor gas transfer but well-preserved lung parenchyma on CT, IPF overlapping with emphysema. Results: Figure 1 shows example images from a cross-section of patients scanned, details of the individual cases will be expanded upon. No adverse events related to imaging were reported. In terms of imaging workflow, scan time average was between 30 min and 1 h 30 min. Patients have been referred from clinics within a 100 km radius and we are also active in enabling novice sites further afield with the technology. Conclusion: Hyperpolarised gas MR provides sensitive, regional images of lung function which can be used to aid in clinical decision making on an individual patient basis. With improvements in gas polarisation, MR hardware and image acquisition techniques routine clinical lung imaging with the cheaper gas isotope 129 Xe is also now possible and large scale clinical evaluation of these methods in patient populations are now underway as part of clinical work up.